Obstetric and neonatal outcome in women with epilepsy - Malik, Roopa; Kumar, Viral; Chaudhary, Susheela; Duhan, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Epilepsy is the second most common neurological disorder complicating pregnancy next to migraine. Both mother and fetus stay at risk due to epilepsy and side effects of antiepileptic’s. This retrospective study was conducted to study fetal and maternal outcome in WWE. Methods: This study was conducted on 55 patients of epilepsy with pregnancy who attended antenatal clinic of our hospital from January 2016 to December 2016. Data was collected using antenatal registers in outdoor settings and medical case sheets in indoor patients and was analyzed statistically. Results: There were a total of 55 WWE in one year duration. Incidence of epilepsy being 0.4% in this study. 11 WWE were not on ante epileptic drug when conceived, while 34 WWE were on ante epileptic drugs when conceived, 8 WWE were newly diagnosed and 2 patients had both psychiatric disorders along with epilepsy. There were 3 IUDs, 4 major congenital malformation and 2 minor malformations. 2 major malformation occurred in patients taking both antipsychotic and ante epileptics since conception. Conclusions: There were a total of 55 WWE in one year duration. Incidence of epilepsy being 0.4% in this study. 11 WWE were not on ante epileptic drug when conceived, while 34 WWE were on ante epileptic drugs when conceived, 8 WWE were newly diagnosed and 2 patients had both psychiatric disorders along with epilepsy. There were 3 IUDs, 4 major congenital malformation and 2 minor malformations. 2 major malformation occurred in patients taking both antipsychotic and ante epileptics since conception.